Development of ASIC1a ligand-gated ion channel drug screening assays across multiple automated patch clamp platforms - Ridley, John; Manyweathers, Sam; Tang, Raymond; Goetze, Tom; Becker, Nadine; Rinke-Weiß, Ilka; Kirby, Robert; Obergrussberger, Alison; Rogers, Marc (Frontiers in Molecular Neuroscience, 2022)
Human acid-sensitive ion channels (ASIC) are ligand-gated receptors expressed widely in peripheral tissues as well as sensory and central neurons and implicated in detection of inflammation, tissue injury and hypoxia-induced acidosis. This makes ASIC channels promising targets for drug discovery in oncology, pain and ischemia, and several modulators have progressed into clinical trials. We describe the use of hASIC1a as a case study for the development and validation of low, medium and high throughput automated patch clamp (APC) assays suitable for the screening and mechanistic profiling of new ligands for this important class of ligand-gated ion channel. Our initial efforts to expand on previous manual patch work describing an endogenous hASIC1a response in HEK cells were thwarted by low current expression and unusual pharmacology, so all subsequent work utilized stable hASIC1a cell lines. Ligand-gated application protocols and screening assays on the Patchliner, QPatch 48, and SyncroPatch 384 were optimized and validated based on pH activation and nM-µM potency of reference antagonists (e.g. Amiloride, Benzamil, Memantine, Mambalgin-3, A-317567, PcTx1). By optimizing single and stacked pipette tip applications available on each APC platform, it was possible to evoke stable pH-evoked current amplitudes during multiple ligand applications and make cumulative EC50 and IC50 determinations with minimized receptor desensitization. Finally, the availability of current clamp on a number of APC platforms raised the possibility of employing the historical technique of input resistance tracking to measure ligand-gated changes in membrane conductance, which was successfully demonstrated for the first time by APC on the Patchliner platform.